TEACHING MULTIMODAL LITERACY THROUGH INTEGRATED LEARNING OF ADVERTISEMENT TEXTS - Muhammad Ramdhan Fathin Al Farabi; Zuliati Rohmah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
Multimodality is a term that has been widely discussed by linguists and semioticians, even education and technology experts in recent years. Then, the selection of multimodal literacy is quite reasonable as an effort to develop student competence. Regarding multimodal texts in comprehensive learning, reading, listening, writing, and speaking are the four modalities that make up multimodal texts and can be integrated into classroom learning. This study aims to analyze what types of multimodal texts are used in this study, how is the application of advertising texts is in integrated learning, and how the students improve their skills in analyzing advertisement texts after being taught using the multimodal texts. The method used in this study is descriptive qualitative through observation during teaching. The participants were the first-semester students in the "learning buddy" program, which totaled 11 people. The research findings showed four types of multimodal advertising text products and multimodal descriptive texts. The multimodal product that is applied includes listening and reading as input. Meanwhile, writing and speaking became the participant's output through the writing of ad text and act it out. The overall results show their progress in understanding and producing the multimodal texts in the class.